KONTRIBUSI EXPERIENTIAL MARKETING STRATEGY PADA LOYALITAS PENGUNJUNG OBJEK WISATA-WISATA DI ROKAN HULU - Hidayat, Afrizal (Fakultas Ekonomi Universitas Pasir Pengaraian, 2015)
This study examines the loyalty of visitors in Rokan Hulu consisting of four objectsthat Hapanasan, Cipogas, Hot Suaman and Aek Martua.Focused in this study is to explorethe contribution of experiential marketing strategy antribut loyalty visitor is using deslriptifquantitative methods and sample collection that visitors encountered during tourist locationstudy with 100 primary responden.Data of distributing questionnaires to the respondentsusing a Likert scale and further descriptive analysis and path analysis or path analysis. Theresults of research that can that attribute experiential marketing strategy consisting sensevariable (X1), feel (X2), think (X3) directly no significant effect on loyalty (Y), but the actvariable (X4), and relate (X5) direct significant effect on loyalty (Y). From the findings inthis study, the researchers suggest Rokan Hulu Government should pay attention to theexisting tourist attraction, especially in the location of this research to develop touristfacilities and infrastructures and services be improved for tourist visitors. If it is addressed,it will provide a good impression so that there will be an attitude of loyalty of the touristvisitors.